Impact of chronic stress on alpha band spectral power and the potential of digital correction of cognitive functions - A. V. Shkabara; G. O. Ushakova; O. V. Severynovska (Regulatory Mechanisms in Biosystems, 2025)
Chronic stress causes hormonal and neurochemical changes, disrupting the balance of excitation and inhibition processes in the brain, which affects the rhythmic activity of neural networks, particularly in terms of power spectral density (PSD) in the alpha frequency range. Also, stress negatively affects cognitive functions, including memory, attention, and executive control. This study examined the relationship between PSD in the alpha band and performance o f visual memory tasks in students with different levels of perceived stress living near the front line of a military conflict. The study included resting-state electroencephalogram (EEG) recordings and cognitive tests before and after a month of training on the CogniFit platform. The results showed that increased alpha-band power in frontal regions was positively associated with visual memory performance in individuals with low stress l e vels. Decreased alpha activity in parietal-occipital regions predicted improved task performance. Men with low stress showed d o minant activation in the right frontal area (Fp2), while women demonstrated more balanced bilateral prefrontal activity. The regre s sion analysis revealed weaker associations between alpha activity and memory performance in the moderate stress group, which may reflect reduced neural efficiency and higher interindividual variability. After cognitive training, both groups showed increased alpha activity in the frontal cortex and decreased alpha power in parietal-occipital regions, reflecting cognitive improvement. This was associated with process automatization and a shift in activity to posterior brain regions in men. In women, prefrontal control increased, indicating more deliberate cognitive regulation. Although the cognitive training effectively improves short-term visual memory, sex-specific neural pa t terns were observed after training, reflecting differences in stress levels and brain organization. The results highlight individual differences in brain neuroplasticity, which should be considered when developing cognitive training programs.